Oncovascular surgery: first two case reports and teamwork perspective - Jacinta Maria Campos; Joana Ferreira; José P. Pinto; André Marçal; Nádia Tenreiro; Tiago Castro; Fernando Próspero; Luís Machado (Angiologia e Cirurgia Vascular)
BACKGROUND: Surgical resection remains the cornerstone for the curative treatment of malignant tumors, such as pancreatic adenocarcinomas. Pancreaticoduodenectomy with vascular reconstruction is a promising approach for tumors invading the portomesenteric vein, and an aggressive surgical approach can improve survival in the mid- and long terms. Thus, vascular surgeons have an increasing role in these surgeries. Therefore, we describe our recent and initial experience and efforts to grow as a true team to offer a better and more systematic response to these patients.